Associated factors to caries experience of children undergoing general anaesthesia and treatment needs characteristics over a 10 year period - Katrin Bekes; Antonia Steuber; Nadia Challakh; Jana Schmidt; Rainer Haak; Valentina Hraský; Dirk Ziebolz (BMC, 2020)
Abstract Background Aim of this study was to describe the characteristics of 1- to 6-year-old children who underwent general anesthesia (GA) in a German specialized pediatric dental institution between 2002 and 2011, and to evaluate the risk factors (age, migration background, nutritional status) for caries experience (dmf-s) in these children. Methods A cross-sectional study with retrospective data collection was designed. Children who underwent comprehensive dental treatment under GA were enrolled in the study. The data were collected from patient records and included personal background: age, sex, dmf-s, nutritional status, reasons for GA and treatments provided. Mann-Whitney-U test, Chi-square tests, and linear regression modelling were applied for statistical analyses. Results 652 children (median age: 3 years [IQR: 2-4], 41.6% female) were treated under GA between 2002 and 2011. Of these, 30.8% had migration background, 17.3% were underweight and 14.8% overweight. The median dmf-s was 28 (IQR: 19-43.5). Univariate, only age and migration showed a significant association with dmf-s (p < 0.01) up to the age of 5 years. In the linear regression analysis, this association of dmf-s with age (OR: 4.04/CI: 2.81-5.27; p < 0.01) and migration (OR: 4.26/CI: 0.89-7.62; p = 0.013) was confirmed. At the patient level, tooth extraction was the most chosen option in both time periods, however, more restorative approaches were taken between 2007 and 2011 including pulp therapy and the use of strip and stainless steel crowns compared to 2002-2006. Conclusions Children aged 1-6 years treated under GA showed a high caries experience (dmf-s), whereby age as well as migration, but not BMI, were relevant risk factors. Although tooth extraction is the first choice in most cases in the first time period, more conservative procedures were performed in the second half of the follow-up period.